2012
DOI: 10.1084/jem.20111721
|View full text |Cite
|
Sign up to set email alerts
|

Cockayne syndrome group B protein prevents the accumulation of damaged mitochondria by promoting mitochondrial autophagy

Abstract: Cells from Cockayne syndrome patients and a mouse model of the disease show increased metabolism as a result of impaired autophagy-mediated removal of damaged mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
134
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(141 citation statements)
references
References 57 publications
7
134
0
Order By: Relevance
“…Indeed, the induction of autophagy reduced mitochondrial loading and mitochondrial membrane potential in CSB cells, revealing that pharmacological modulation of this pathway is a promising approach. 109 Moreover, autophagy also has a role in stem cells maintenance, 110 suggesting that this pathway may also fight accelerated aging by maintaining the health of the stem cell population, avoiding loss of regenerative potential. 111 Accumulation of oxidatively generated damage has been implicated in several neurodegenerative diseases such as Parkinson's and Alzheimer's diseases.…”
Section: Parpmentioning
confidence: 99%
“…Indeed, the induction of autophagy reduced mitochondrial loading and mitochondrial membrane potential in CSB cells, revealing that pharmacological modulation of this pathway is a promising approach. 109 Moreover, autophagy also has a role in stem cells maintenance, 110 suggesting that this pathway may also fight accelerated aging by maintaining the health of the stem cell population, avoiding loss of regenerative potential. 111 Accumulation of oxidatively generated damage has been implicated in several neurodegenerative diseases such as Parkinson's and Alzheimer's diseases.…”
Section: Parpmentioning
confidence: 99%
“…2,22,23,36,52,58,64,69 However, in vivo studies of rodent models did not show a consistent result for autophagy regulation by lithium, although behavioral abnormalities of all studies were improved. 46,49,54,66,72 This discrepancy is at least partly because of the lithium concentration. In tauopathy model mice, 4-month oral lithium treatment led to a 0.2 mM lithium plasma level and enhanced autophagy.…”
Section: Controversiesmentioning
confidence: 99%
“…metabolism in CSB m/m mice and CSB-deficient cells. 66 In CSBdeficient cells, damaged mitochondria and free radical production are increased and autophagy is downregulated. Lithium chloride or rapamycin 10 mM reverses the bioenergetics phenotype of CBS-deficient cells.…”
mentioning
confidence: 99%
“…Prior literature revealed mitochondrial deficits in A-T. 2 Since there are well-established links between DNA repair defects, neurodegeneration and mitochondrial dysfunction, 3,4 we focused our attention on mitochondria. In 2 other DNA repair-deficient syndromes, Cockayne Syndrome (CS), 4,5 and Xeroderma Pigmentosum group A (XPA), 3 we reported that persistent nuclear DNA damage created a signal to mitochondria, which we called nuclear to mitochondrial (NM) signaling.…”
mentioning
confidence: 99%
“…In 2 other DNA repair-deficient syndromes, Cockayne Syndrome (CS), 4,5 and Xeroderma Pigmentosum group A (XPA), 3 we reported that persistent nuclear DNA damage created a signal to mitochondria, which we called nuclear to mitochondrial (NM) signaling. 6 Nicotinamide adenine dinucleotide (NAD C ), an important metabolite in all human cells, was the signaling molecule.…”
mentioning
confidence: 99%